The network of firms implied by the news - Gustavo Schwenkler; Hannan Zheng (European Systemic Risk Board (ESRB), European System of Financial Supervision, 2020)
We show that the news is a rich source of data on distressed firm links that drive firm- level and aggregate risks. The news tends to report about links in which a less popular firm is distressed and may contaminate a more popular firm. This constitutes a contagion channel that yields predictable returns and downgrades. Shocks to the degree of news-implied firm connectivity predict increases in aggregate volatilities, credit spreads, and default rates, and declines in output. To obtain our results, we propose a machine learning methodology that takes text data as input and outputs a data-implied firm network.
Keywords: E32; E44; L11; G10; C82; 330; Networks; contagion; predictability; risk measurement; machine learning; natural language processing